2011
DOI: 10.3329/jbas.v35i1.7976
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Growth Analysis of two Varieties of Rice Following Naphthalene Acetic Acid Application

Abstract: A pot experiment showed that 100 and 200 ppm naphthalene acetic acid (NAA) plant height, number of leaves per plant and number of tillers per plant were found to increase due to 100 ppm NAA only in BRRI dhan-29 (V 1 ) and varied significantly at 60 DAS. Total dry matter (TDM) was found to increase up to harvest due to both the treatments in V 1 , whereas, in BRRI dhan-50 (V 2 ) also increased at 15 and 30 DAS and the variation was non-significant. There was an increasing tendency in leaf area per plant due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 6 publications
2
14
0
Order By: Relevance
“…Treatment T3 produced tallest plants from the age of 35 DAS till harvest, whereas, plants receiving T4 treatment showed minimum height at all the ages except at 28 DAS. Similar results of both increase and decrease in plant height have also been reported by Alam et al (5) in wheat, Akter (9) in maize and Jahan and Adam (11) in rice. Results obtained during the present investigation showed that number of tillers per plant and number of leaves per plant were higher due to T1 and T2 treatments at 7 and 14 DAS, whereas, other two treatments resulted decreases at all stages of growth (Tables 2, 3).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Treatment T3 produced tallest plants from the age of 35 DAS till harvest, whereas, plants receiving T4 treatment showed minimum height at all the ages except at 28 DAS. Similar results of both increase and decrease in plant height have also been reported by Alam et al (5) in wheat, Akter (9) in maize and Jahan and Adam (11) in rice. Results obtained during the present investigation showed that number of tillers per plant and number of leaves per plant were higher due to T1 and T2 treatments at 7 and 14 DAS, whereas, other two treatments resulted decreases at all stages of growth (Tables 2, 3).…”
Section: Resultssupporting
confidence: 88%
“…Harsharn and Gill (6) reported about the positive effect of NAA on the number of leaves per plant in wheat and barley. Both increase and decrease in number of leaves per plant has also been reported in maize (9) and in rice (11) .…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Adam and Jahan (2011) reported that in BRRI dhan 29, yield and yield attributes increased following 100 and 200 ppm NAA application, whereas, most of the yield parameters decreased in BRRI dhan 50. In a comparative growth analysis, Jahan and Adam (2011) observed differences in responses between two varieties of rice and between the two concentrations of NAA where, better stimulation was due to 100 ppm. The favourable effect of NAA in enhancing nutrient uptake by rice is also reported (Adam et al 2012).…”
Section: Introductionmentioning
confidence: 99%